Collaboration between pathomorphologists and clinicians in the malignant melanoma diagnostic process - Patera, Janusz; Kozłowski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2003)
The collaboration between clinicians and pathomorphologists in the malignant melanoma diagnostic process is necessary and should start at the stage of planning the method and the place to obtain a biopsy material. Clinicians are responsible for proper sampling of the biopsy material, its fixation and transport to the Department of Pathomorphology. Clinicians should be aware of the fact that observing these rules makes the pathomorphological examination successful. 10% phosphate-buffered formalin can be used for the routine fixation of all specimens. For the application of molecular biology methods it is required to freeze fresh tissues. Whereas the examination with the use of Electron Microscopy has to be performed on the biopsy material fixated with glutaraldehyde, and the tissue sample size must be about 1 mm3. Clinicians should properly complete all clinical data and that is one of the most important requirements. The pathomorphologists in their diagnosis have to present all data obtained during histopathological examinations which allow for the precise staging of malignant melanoma and prognostic and predictive indices.